Factors Associated With Job Satisfaction Among Degree Nurses Working In Clinical Areas At Hospital Universiti Sains Malaysia, Kelantan - Kesom AIP Eh Bek; Chan Siok Gim
The purpose of this quantitative study is to identify factors affecting job satisfaction among sixty six degree nurses working in clinical area at Hospital Universiti Sains Malaysia. The six components examined were pay, autonomy, task requirements, professional status, interaction and organization policies. Pay component was ranked as least satisfying followed by organizational policies, task requirements, autonomy, interaction, with professional status as most satisfying component. The range of score for this study was 105 to 178 with average total score of 139. These figures show low levels of satisfaction among the nurses. Correlation between duration of working hours after getting their degrees and job satisfaction indicated negative but significant relationship between two variables; respondents with increasing years work experience as a degree holder became less satisfied with their job. There were significant differences in job satisfaction between nurses on shift duty as opposed to those working in the office hours, and between those working in critical versus non-critical areas. However, there were neither significant associations nor differences found for other demographic variables. This study presented findings that are essential for healthcare and nursing administrators to initiate interventions based on evidence with regards to the plight of degree nurses in their opportunities for upgrading themselves.